21st century guidebook to fungi - Moore, D. (David), 1942-; Robson, G. D. (Geoffrey D.); Trinci, A. P. J. (Cambridge ; New York : Cambridge University Press, 2011)
'Fungi have their own unique cell biology and life cycle, but also play critical roles in wider biological systems. This textbook provides an all-round view of fungal biology, ranging in scope from the evolutionary origins of fungi and other eukaryotes more than a billion years ago, to the impact fungi have on our everyday lives. Bringing mycology teaching right up to date, this unique systems biology approach emphasises the interactions between fungi and other organisms to illustrate the critical roles that fungi play in every ecosystem and food web. With more than 60 colour figures, examples of computational modelling and resource boxes directing students to areas of interest online, this uniquely modern textbook gives students an appreciation of fungi both at the organism level and in the context of wider biology. A companion CD features a hyperlinked version of the book and the fully integrated World of Cyberfungi website'--
Book is accompanied by 1 CD entitled'21st century guidebook to fungi' bearing the same call number and available at Koleksi Media.
Includes bibliographical references and index.
Keywords: Fungi; Fungal molecular biology